1998
DOI: 10.1097/00006199-199807000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Individualizing Nighttime Incontinence Care in Nursing Home Residents

Abstract: Incorporating this intervention component into more comprehensive efforts to improve sleep and evaluating the long-term effects of the intervention on skin health are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(100 citation statements)
references
References 9 publications
1
99
0
Order By: Relevance
“…It is not only what is being done, but also to how it is being done*the essence of quality Levy-Storms et al, 2007;Miller, 2007;O'Connor & Ribgy, 1996;Sachweh, 1998). Our findings suggest that a connection can be made between communication and quality of care in that communication is a core element of IC, which has been shown to improve quality of care (Schnelle, Cruise, Alessi, Al-Samarrai, & Ouslander, 1998;van Servellen, 1997). Of course, IC is one of many issues (e.g., staffing ratios, poor pay) affecting the quality of care .…”
Section: Practical Implicationsmentioning
confidence: 77%
“…It is not only what is being done, but also to how it is being done*the essence of quality Levy-Storms et al, 2007;Miller, 2007;O'Connor & Ribgy, 1996;Sachweh, 1998). Our findings suggest that a connection can be made between communication and quality of care in that communication is a core element of IC, which has been shown to improve quality of care (Schnelle, Cruise, Alessi, Al-Samarrai, & Ouslander, 1998;van Servellen, 1997). Of course, IC is one of many issues (e.g., staffing ratios, poor pay) affecting the quality of care .…”
Section: Practical Implicationsmentioning
confidence: 77%
“…There is no shortage of factors that result in nocturnal awakenings in the elderly population. These may include age-dependent intrinsic lightening of sleep homeostatic processes (8,9), chonobiologic changes (10), higher susceptibility to arousal from sources such as noise and light (11, 12), awakenings from primary medical conditions (e.g., osteoarthritis, gastroesophageal reflux) (13, 14), or specific sleep disorders such as sleep apnea (1517). In this scenario, an older individual may awaken from one or more of these causes, perceive a full bladder, and then voluntarily elect to arise from bed and void.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding possibility (a), several trials of muscarinic antagonists and desmopressin including sizeable numbers of adults age 50 and above have reported longer duration of first sleep episode before first nocturnal void (1821), reduced diary-defined number of awakenings (22) or global self-reported improvements in sleep (23–27), but at least one trial showed apparent worsening of sleep due to dry mouth from such medication (28). Daytime behavioral interventions targeting nocturnal bladder control in incontinent geriatric patients have shown mixed results on nocturnal incontinence and do not assess sleep per se (29), though one nocturnal incontinence intervention noted fewer awakenings at night (12). Even fewer studies have addressed possibility (b); however, decreased nocturia episodes and nocturnal urine production have been associated with successful treatment of sleep apnea with nasal continuous positive airway pressure (15, 30, 31).…”
Section: Discussionmentioning
confidence: 99%
“…32,37-39 Pharmacological treatments have also been shown to be effective, particularly anticholinergic agents, but side effects are a concern and warrant close monitoring. 40 Schnelle et al 41,42 have also demonstrated the importance of individually tailored care for good UI outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…The levels include continent (defined as complete control), usually continent (incontinent episodes once a week or less), occasionally incontinent (2 or more times a week but not daily), frequently incontinent (tended to be Vol. 41,No. 4 URINARY INCONTINENCE QUALITY MEASURES incontinent but some control present), and incontinent (had inadequate control, multiple daily episodes).…”
Section: Variables Definitionsmentioning
confidence: 99%